DI-003 Antiretroviral compliance: comparative analysis. (24th February 2014) - Alcobia, A; Duarte, H; Soares, A; Videira, G
Abstract : Background: The management of antiretroviral treatment (ART) must be judicious in all clinical and societal aspects, as it is very expensive. In times of budgetary containment all efforts must be made to optimise ART. The proposed intervention at this level, by the Pharmaceutical Services Hospital Garcia de Orta (HGO), related to improving adherence and analysis of the role of a single daily dose or the use of a single tablet daily. Purpose: To evaluate the rate of compliance with antiretroviral treatment according to the treatment regimen. Materials and methods: A retrospective observational study was made using the IMSHealth HIVAnalytics platform. The compliance rate of all adult patients followed in the infectiology service was calculated between August 2011 and June 2013. Compliance was defined as staying at least 3 months on a given therapeutic regimen. Statistical analysis was performed using SPSS 22.0. Results: This study included 1007 patients with a mean age of 47.3 ± 11 years, 66.6% male. During the study period 878 patients (87.2%) remained on the same regimen. We determined the average compliance rates (ACR) of the 10 regimens most frequently prescribed in our hospital: ABC/3TC + EFV (N = 57; ACR = 91.6%); EFV/TDF/FTC (N = 421; ACR = 89 9%), AZT + 3 TC + NVP (N = 63; ACR = 87.9%); ATV/r + ABC/3TC (N = 59; ACR = 87.6%); ABC/3TC + NVP (N = 92; ACR = 87.5%); DRV/r + ABC/3TC (N = 96; ACR = 86.8%); ATV/r + TDF/FTC (N = 55; ACR = 81.8%); LPV/r + ABC/3TC (N = 64; ACR = 81.0%), LPV/r + AZT + 3 TC (N = 162; ACR = 77.9%), LPV/r + AZT/3TC (N = 67; ACR = 76.8%). The total average compliance rate was 85.9%. There were no statistically significant differences in ACR between EFV/TDF/FTC (single daily dose scheme) and EFV + ABC/3TC (p value 0.304) statistical test Mann-Whitney. [3TC = lamivudine, ABC = abacavir, ATV = atazanavir, AZT = zidovudine; DRV = darunavir; EFV = efavirenz, FTC = emtricitabine; LPV = lopinavir; NVP = nevirapine, r = ritonavir, TDF = tenofovir] Conclusions: Treatment-associated cost is the main determinant of the overall cost of monitoring patients infected by HIV, and we should include variables in addition to price, namely compliance with treatment. Our data suggest there were no significant differences in ACR, in order to pre-exclude any of the 10 most used schemes in HGO, even when multiple-dose schemes were compared with a single daily dose scheme. No conflict of interest.